A Perspective on a Two-stent Approach in Bifurcation Cases - Gherasie Flavius-Alexandru; Chioncel Valentin (Sciendo, 2024)
Bifurcation lesions are the cause of 20% of all percutaneous coronary interventions, representing a complex category associated with lower procedure success rates and higher restenosis rates. However, the optimal approach to bifurcation needs further research. This paper aims to determine the optimal method for implementing a two-stent strategy in bifurcation cases. It desires to identify the characteristics that can guide our approach and the outcomes that can be expected. This paper also highlights relevant trials that support the findings.